ChemInform Abstract: Recent Progress in Obtaining Semiconducting Single‐Walled Carbon Nanotubes for Transistor Applications. Issue 9 (February 2016) - Islam, Ahmad E.; Rogers, John A.; Alam, Muhammad A.
Abstract: Review: 282 refs.